A Preliminary Investigation of the Effects of a Western Diet on Hippocampal Volume in Children - Stadterman, Jill; Belthoff, Kyrstin; Han, Ying; Kadesh, Amanda D.; Yoncheva, Yuliya; Roy, Amy Krain (Frontiers in Pediatrics, 2020)
Introduction: Over the course of the 20th century, there has been a sharp increase in the consumption of saturated fat and refined sugars. This so-called “western diet” (WD) has been extensively linked to biological alterations and associated functional deficits in the hippocampus of animals. However, the effects of a WD on the human hippocampus are less well characterized. This preliminary study aimed to extend prior animal work by investigating the effects of a WD on hippocampal volume in children. Methods: Twenty-one healthy children (ages 5-9) completed a structural T1-weighted magnetic resonance imaging scan. Bilateral hippocampal volumes (as regions-of-interest) and bilateral amygdala volumes (as medial temporal lobe control regions-of-interest) were calculated. WD variables were derived from the parent-completed Youth/Adolescent Food Frequency Questionnaire. Specifically, variables were calculated as percent of daily calories consumed from sugars, fats, or the combination (WD). Results: While the relationships between overall WD consumption and bilateral hippocampal volumes were not significant, increased fat consumption was significantly related to decreased left hippocampal volume. Sugar consumption was not related to hippocampal size. Control region volumes were not related to any diet variables. Discussion: This study is the first to directly link diet – specifically fat consumption – to decreased left hippocampal volume in children. This extends previous work showing smaller left hippocampal volume related to obesity in pediatric samples. Though preliminary, findings represent an important step towards understanding the impact of diet on child brain development.